Perlindungan Hukum terhadap Pemuda Dari Kejahatan Terorisme Di Wilayah Hukum Provinsi Jambi - Ferdricka Nggeboe; Reza Iswanto; Sriayu Indah Puspita (Universitas Batanghari Jambi, 2020)
Research on legal protection against youth from terrorism crimes in the jurisdiction of Jambi Province aims to determine the form of protection from the government and law enforcement in Jambi Province. The object of his research is legal protection for youth. The problem in this case is how the legal protection of youth from terrorism crimes in the jurisdiction of Jambi Province. The research method is normative so that this research is more descriptive qualitative in nature and sourced from literature. The approach is a case approach and the data collection technique is document study and data analysis is done qualitatively. The result of his research is that legal protection for youth from terrorism crimes in the jurisdiction of Jambi Province is carried out by means of preventive means, namely the government issues legal rules related to terrorism crimes, namely Law Number 5 of 2018 to protect youth who are victims of terrorism crimes, then law enforcement officers and The Counter-Terrorism Communication Forum conducts outreach / counseling related to terrorism crimes, while the repressive form is the Jambi Provincial government and law enforcement officials to ensnare perpetrators of terrorism crimes by imposing criminal sanctions as regulated in Law Number 5 of 2018 concerning Amendments to Law Number 15 2003 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2002 Concerning the Eradication of Criminal Acts of Terrorism into Law.